Pelatihan Internet Untuk Pengembangan SDM PT. Mitra Atlantic Nusantara Cengkareng Jakarta Barat - Arsanto Narendro; Suwasti Broto; T.W. Wisjhnuadji (CV. Multi Kreasi Media, 2024)
The development of human resources (HR) is a crucial aspect of enhancing the competitiveness of an organization or a country. In the digital era, internet training has become one of the essential elements in HR development. This training not only improves individuals' technical skills but also broadens their perspectives and adaptability to technological changes.As information technology continues to advance, the ability to use the internet effectively has become a necessity. Appropriate internet training can assist individuals in accessing information, communicating efficiently, and improving work productivity. Additionally, this training contributes to innovation and creativity across various fields, including business, education, and healthcare.